ENHANCING ENGINEERING STUDENTS’ ENGLISH LANGUAGE SKILLS THROUGH PROJECT-BASED LEARNING AND TECHNOLOGY INTEGRATION - Srikanth, Goshika; Palwekar, Sanjay D. (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study examines the effectiveness of project-based learning (PBL) and technology integration in improving engineering students’ English language skills. A mixed approach was used, combining quantitative and qualitative data. The results show that the integration of PBL and technology greatly improves English, motivation and collaboration skills. This study provides an outline of PBL and technology integration to support language learning and improve the proficiency of the language of engineering students.